Pengaruh Kompensasi, Teamwork, dan Pengembangan Karir Terhadap Keterikatan Karyawan di PT Sangsaka Surya Karunia Jogja: Kompensasi, Teamwork, Pengembangan Karir, dan Keterikatan Karyawan - Barzah, Sofiatul; Susilowati, Fitri; Sumarmi, Saptaningsih (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to determine the effect of compensation, teamwork, career development on employee engagement at PT Sangsaka Surya Karunia Jogja. This study uses a causal associative research method with a quantitative approach using the SPSS ver 21.0 program. The study population consisted of 104 employees of PT Sangsaka Surya Karunia Jogja and a sample of 83 respondents using a non-probability sampling technique, using a purposive sampling approach. Data collection techniques were carried out by means of interviews and questionnaires. The analysis technique uses multiple linear regression. The results showed that compensation had a significant positive effect on employee engagement with a regression coefficient of 0.110 and sig 0.048. Teamwork has a sig positive effect on employee engagement with a regression coefficient of 0.653 and sig 0.000. Career development has a significant positive effect on employee engagement with a regression coefficient of 0.154 and sig 0.008. The results of the study simultaneously compensation, teamwork, and career development have an effect on employee engagement with a sig value of 0.000 and F count of 32,360. The effect of compensation, teamwork, and career development on employee engagement is shown by the Adjusted R Square value of 53.4%, the remaining 46.6% is influenced by other variables not examined in this study. Therefore, all hypotheses in this study are accepted.